1999
DOI: 10.1097/00001888-199909000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with changing levels of interest in primary care during medical school

Abstract: Schools wishing to graduate more students who enter primary care specialties may want to raise the number of primary care elective courses to increase students' interests, and to help them choose to enter and remain in primary care specialties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…17 Two studies found that students rejecting family medicine were concerned about a lack of prestige, low income potential, and low intellectual content of the specialty. 24,37 Generalist orientation was found to predict choice of a family medicine residency at the point of selection of a residency. 50 These studies suggest that perceptions about the characteristics and content of specialties influence specialty decisions, although the available research is extremely limited in scope.…”
Section: Knowledge Of Content and Characteristics Of Specialtiesmentioning
confidence: 99%
See 2 more Smart Citations
“…17 Two studies found that students rejecting family medicine were concerned about a lack of prestige, low income potential, and low intellectual content of the specialty. 24,37 Generalist orientation was found to predict choice of a family medicine residency at the point of selection of a residency. 50 These studies suggest that perceptions about the characteristics and content of specialties influence specialty decisions, although the available research is extremely limited in scope.…”
Section: Knowledge Of Content and Characteristics Of Specialtiesmentioning
confidence: 99%
“…17,24,34 -36 One retrospective study of family physicians did find that a majority reported interest increasing during medical school. 37 Another study demonstrated that the ability to attract students to family medicine during medical school is positively related to the family medicine output of the school.…”
Section: Career Intentions On Entry To Medical Schoolmentioning
confidence: 99%
See 1 more Smart Citation
“…13 The study by Xu et al may clarify this issue. 22 They asked general practitioners in the USA whether they had any strong inter- The appeal of FM increased over the years of study (36.7%, 41.7%…”
mentioning
confidence: 99%
“…La elección de especialidad refleja a lo que han sido expuestos los graduados, las modas y la percepción sobre las especialidades como profesiones sanitarias 2 . Xu et al 16 , en una encuesta que hicieron a médicos generalistas de Estados Unidos, preguntaban si habían tenido mucho interés por la AP antes de su formación universitaria y si esa inclinación había variado durante la formación, con especial atención a sus experiencias clínicas en este ámbito asistencial. A partir de las respuestas de 1.561 participantes, encontraron que el 45 % había aumentado su interés por la AP durante su formación de grado; en el 48 % la inclinación había permanecido constante y en el 7 %, había disminuido.…”
unclassified